Nieve y neón - Ferrero, Jesús, 1952- (Madrid : Siruela, 2015)
The origin's of Ferrero's detective Ágata Blanc, shown as a teenager in Berlin, just after the fall of the Wall.
Online resource; title from ePub title page (Digitalia, viewed April 10, 2017)
Keywords: Young adults -- Germany -- Berlin -- Fiction; Organized crime -- Germany -- Berlin -- Fiction; Berlin (Germany) -- Fiction; Detective and mystery fiction; Electronic books